2017
DOI: 10.1016/j.vaccine.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Potency of whole virus particle and split virion vaccines using dissolving microneedle against challenges of H1N1 and H5N1 influenza viruses in mice

Abstract: Transdermal vaccination using a microneedle (MN) confers enhanced immunity compared with subcutaneous (SC) vaccination. Here we developed a novel dissolving MN patch for the influenza vaccine. The potencies of split virion and whole virus particle (WVP) vaccines prepared from A/Puerto Rico/8/1934 (H1N1) and A/duck/Hokkaido/Vac-3/2007 (H5N1), respectively, were evaluated. MN vaccination induced higher neutralizing antibody responses than SC vaccination in mice. Moreover, MN vaccination with a lower dose of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
(35 reference statements)
1
9
0
Order By: Relevance
“…In particular, studies of influenza vaccination that compared MAP injection and a no-treatment group found that the MAP application conferred greater protective immunity. 28,29 Similar observations were documented when comparing MAP injection with subcutaneous injection 30,31 and intranasal administration. 32 Notably, the MAP application induced not only comparable protective efficacy [33][34][35][36][37] but also better protection event [38][39][40][41] compared to intramuscular (IM) administration.…”
Section: Preclinical Studies Of Vaccine Mapsupporting
confidence: 67%
“…In particular, studies of influenza vaccination that compared MAP injection and a no-treatment group found that the MAP application conferred greater protective immunity. 28,29 Similar observations were documented when comparing MAP injection with subcutaneous injection 30,31 and intranasal administration. 32 Notably, the MAP application induced not only comparable protective efficacy [33][34][35][36][37] but also better protection event [38][39][40][41] compared to intramuscular (IM) administration.…”
Section: Preclinical Studies Of Vaccine Mapsupporting
confidence: 67%
“…The influenza A virus PR8 (H1N1) strain is lethal in mice, who succumb within 8 dpi in the presence of a concentration of 10 MLD 50 [ 17 ]. Influenza onset correlates with inflammatory cytokine expression, and neuroinflammation due to influenza virus infection releases inflammatory cytokines and can cause lung tissue damage [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Virus challenge in mice was conducted as previously described [ 17 ]. After 7 weeks of feeding the mice a standard or 25(OH)D 3 -supplemented diet, PR8 (H1N1) was inoculated intranasally using 10 times the 50% mouse lethal dose (MLD 50 ) in 30 µL per mouse under anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…Cutaneous antigen delivery 12 using variety of devices and vaccines 13 including influenza vaccines 14 20 is an active and promising area of research with important implications for public health. We 17 19 , 21 23 and other investigators 24 28 have observed improved immune responses to influenza vaccination by MNPs. Improved response to skin-delivered antigens occurs due to a network of immunoregulatory cells in skin 29 31 including specialized sets of resident antigen-presenting cells (APC) 32 .…”
Section: Introductionmentioning
confidence: 58%